Let there be light [videorecording (DVD)] - Huston, Walter, 1884-1950; Simon, Benjamin (Dreamscape film series., 2019)
"John Huston's stirring documentary about returning war veterans was suppressed by the United States government for over thirty years after it was produced. Every man has his breaking point, says narrator Walter Huston. These in the fulfillment of their duties as soldiers were forced beyond the limits of human endurance. Filmed at two Long Island locations (Edgewood State Hospital and Pilgrim State Hospital), this account of ex-soldiers struggling with emotional trauma is unforgettable."--